Heterostructure Mg-Sc-Y anode material, battery, application and preparation method

By doping Sc and Y elements into the anode material of the magnesium air battery, a heterostructure Mg-Sc-Y anode material is formed, which solves the problems of low discharge voltage and low anode efficiency of the anode material of the magnesium air battery, and achieves the effects of high reactivity, low corrosion rate and high anode utilization rate.

CN119812294AActive Publication Date: 2025-04-11TAIYUAN UNIVERSITY OF TECHNOLOGY +1
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202510304973.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-14
Publication Date
2025-04-11
Estimated Expiration
2045-03-14

AI Technical Summary

Technical Problem

Magnesium air battery anode materials face the problems of low discharge voltage and low anode efficiency in large-scale applications, mainly due to the adhesion effect of discharge products and the hysteresis anode reaction kinetics, and the negative difference effect leads to anode hydrogen evolution and self-corrosion.

Method used

Using a heterostructure Mg-Sc-Y anode material, the microstructure structure is changed by doping an appropriate amount of rare earth elements Sc and Y into the magnesium matrix to form a heterostructure composed of elongated deformation grains and fine isometric grains, thereby improving chemical activity and corrosion resistance.

Benefits of technology

The coordinated improvement of discharge voltage and anode efficiency is achieved, which significantly improves the comprehensive discharge performance of magnesium air batteries, reduces the thermodynamic tendency of microcouple corrosion, and reduces production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119812294A_ABST
    Figure CN119812294A_ABST
Patent Text Reader

Abstract

The invention discloses a heterostructure Mg-Sc-Y anode material, a battery, application and a preparation method, and belongs to the technical field of magnesium air battery anode materials, the anode material comprises the following components by mass: 0.1% of scandium, 0.1% of yttrium, and the balance magnesium. The microalloying design is adopted, a very small amount of rare earth elements are added into pure magnesium, and the cost of the anode material and the galvanic corrosion tendency of the anode material are reduced. A heterogeneous microstructure is designed through a short-process technology of solid solution and extrusion after smelting, and the heterogeneous microstructure is composed of elongated deformed crystal grains and fine equiaxed crystal grains. According to the invention, the corrosion resistance of the anode of the magnesium-air battery is enhanced, the anode reaction kinetics is activated, the effective anode reaction area is increased, the side reaction of self-corrosion hydrogen evolution is reduced, and the synergistic improvement of the discharge voltage and the anode efficiency of the battery is realized. The invention is convenient for preparation and application, and has significant meaning for prolonging the discharge life of the magnesium-air battery and large-scale popularization.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of magnesium-air battery anode materials, and in particular relates to a heterostructured Mg-Sc-Y anode material, a battery, and an application and preparation method thereof. Background Art

[0002] In order to cope with the crisis of climate change and fossil fuel shortage, countries are actively seeking new energy devices and increasing their share in total energy production. Metal-air batteries have become a new energy storage and conversion device with great application potential due to their high energy density, easy access to raw materials, and pollution-free production process.

[0003] Magnesium and its alloys are ideal anode materials for metal-air batteries due to their relatively negative standard electrode potential (-2.37V vs. standard hydrogen electrode) and high theoretical specific energy (6.8kWh / kg). At the same time, my country has abundant magnesium resources, making the large-scale promotion of such batteries low-cost and promising.

[0004] However, the current large-scale application of magnesium-air battery anode materials still faces the following problems: on the one hand, the adhesion effect of discharge products and the sluggish anode reaction kinetics reduce the surface reaction area and increase the internal resistance of the system, making the actual discharge voltage far lower than the theoretical value; on the other hand, the negative difference effect (NDE) induces severe anode hydrogen evolution and self-corrosion, reducing the anode efficiency.

[0005] Therefore, the development of high-performance magnesium alloy anode materials has become one of the hot spots and difficulties in the research of magnesium-air batteries, and is also the key to improving their discharge performance. It is urgent to design new magnesium-based anode materials with high reactivity, slow corrosion rate and high anode utilization to solve the constraints between discharge voltage and anode efficiency. Summary of the invention

[0006] In order to solve the above technical problems, the present invention proposes a heterostructured Mg-Sc-Y anode material, a battery, and an application and preparation method to solve the contradiction between the actual discharge voltage and the energy conversion efficiency in the current magnesium air battery application.

[0007] To achieve the above object, the present invention provides a heterostructured Mg-Sc-Y anode material, comprising the following components in mass percentage: scandium: 0.1%, yttrium: 0.1%, and the balance being magnesium.

[0008] In a possible implementation, the heterostructured Mg-Sc-Y anode material presents a heterogeneous microstructure composed of elongated deformed grains and fine equiaxed grains.

[0009] In a possible implementation, the average grain size of the fine equiaxed grains is 1.30±0.01 μm, and the aspect ratio of the elongated deformed grains is 6.73±0.05.

[0010] The present invention also provides a method for preparing the above-mentioned heterostructure Mg-Sc-Y anode material, comprising the following steps: (1) Under a protective atmosphere, a magnesium block, a magnesium-scandium master alloy and a magnesium-yttrium master alloy are melted to obtain an alloy liquid, stirred and allowed to stand, scum on the surface is scraped off, a refining agent is added to the alloy liquid for refining, and after the refining is completed, casting and cooling are performed in sequence to obtain a Mg-Sc-Y alloy ingot; (2) Under a protective atmosphere, performing a double-stage solid solution treatment on the Mg-Sc-Y alloy ingot to obtain a solid solution matrix; (3) The solid solution matrix is ​​subjected to extrusion processing to obtain an extruded rod, which is a heterostructured Mg-Sc-Y anode material.

[0011] In a possible implementation, in step (1), the protective atmosphere is carbon dioxide and sulfur hexafluoride, and the volume ratio of carbon dioxide to sulfur hexafluoride is (35-45):1; In step (2), the protective atmosphere is argon.

[0012] In a possible implementation, in step (1), the refining agent is a mixture of MgCl2, KCl, BaCl2 and CaF2, and the mass ratio of MgCl2, KCl, BaCl2 and CaF2 is 46:40:8:6; The refining temperature is 740° C., and the refining time is 1-2 minutes.

[0013] In a possible implementation, in step (2), the steps of the double-stage solution treatment are: a first solution treatment and a second solution treatment performed sequentially; The temperature of the first solution treatment is 310-330°C, and the holding time of the first solution treatment is 50-70min; The temperature of the second solution treatment is 480-520° C., and the holding time of the second solution treatment is 350-370 min.

[0014] In a possible implementation, in step (3), the temperature of the extrusion treatment is 240-250° C., the speed of the extrusion treatment is 0.08-0.12 mm / s, and the extrusion ratio is 15:1-17:1.

[0015] The present invention also provides an application of the above-mentioned heterostructure Mg-Sc-Y anode material in a magnesium-air battery.

[0016] The present invention also provides a magnesium-air battery, comprising the above-mentioned heterostructure Mg-Sc-Y anode material.

[0017] Compared with the prior art, the present invention has the following advantages and technical effects: The present invention provides a heterogeneous structure Mg-Sc-Y anode material, comprising the following components in mass percentage: magnesium: 99.8%, scandium: 0.1%, yttrium: 0.1%. The present invention changes the microstructure of the magnesium alloy by doping appropriate amounts of rare earth elements Sc and Y into a pure magnesium anode for microalloying. The Sc element and the Y element have a high solid solubility in the Mg matrix. The Sc and Y atoms can simultaneously improve the chemical activity and corrosion resistance of the matrix during the discharge process, thereby achieving a synergistic improvement in the discharge voltage and anode efficiency; at the same time, the addition of rare earth elements also significantly refines the grains and effectively activates the discharge process. The content of the added alloying elements does not exceed 0.1%, which not only reduces the production cost of the magnesium anode material, but also does not produce a second phase, greatly reducing the thermodynamic tendency of microgalvanic corrosion.

[0018] The heterostructured Mg-Sc-Y anode material does not have a precipitated phase, and the organization is regulated through the aforementioned processing technology to form a heterostructure, that is, it is composed of elongated deformed grains and fine equiaxed grains; the average grain size of the fine grains is 1.30±0.01μm, while the aspect ratio of the deformed coarse grains is 6.73±0.05.

[0019] The heterostructured Mg-Sc-Y anode material provided by the present invention achieves a synergistic improvement in discharge voltage and anode efficiency.

[0020] The invention uses magnesium block, magnesium-scandium master alloy and magnesium-yttrium master alloy as raw materials, and prepares a magnesium-air battery anode material with excellent discharge performance through melting, refining, two-stage solid solution treatment and extrusion treatment. The preparation method has a short process flow, is simple and efficient, and has a low preparation cost.

[0021] The present invention adopts a process flow of direct extrusion after double-stage solid solution treatment, which shortens the preparation process, realizes a heterogeneous microstructure after extrusion treatment, and improves the comprehensive discharge performance of the magnesium-air battery anode material.

[0022] After extrusion treatment, the solid solution matrix obtains a mixed crystal structure of heterogeneous lamellar layers, which significantly improves the anode dissolution kinetics, effectively inhibits anode hydrogen evolution and block effect, and improves the discharge performance of the battery.

[0023] The low alloy magnesium-air battery anode material provided by the present invention is applied to a magnesium-air battery. When used as an anode, the current density is 0.5 mA·cm -2 When the discharge voltage is 1.6482V, the anode utilization rate is 33.44%.-2 At this current density, the discharge voltage reached 1.4252V, the anode utilization rate was 60.23%, and the energy density reached 1915.59mW·h·g -1 . BRIEF DESCRIPTION OF THE DRAWINGS

[0024] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0025] Figure 1 This is a metallographic microstructure diagram of the heterostructured Mg-Sc-Y anode material obtained in Example 1 of the present invention; Figure 2 This is a graph showing the average grain size of fine crystals of the heterostructured Mg-Sc-Y anode material obtained by statistics in Example 1 of the present invention; Figure 3 Graph showing the characterization results of the heterostructured Mg-Sc-Y anode material obtained in Example 1 of the present invention; wherein a is a SEM microstructure graph, and b is an XRD graph; Figure 4 This is a potentiodynamic polarization test diagram of the heterostructure Mg-Sc-Y anode material obtained in Example 1 of the present invention. DETAILED DESCRIPTION

[0026] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0027] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0028] The "magnesium block", "magnesium-scandium master alloy" and "magnesium-yttrium master alloy" used in this article are all high-purity metal materials, which can be obtained by technical personnel in this field through commercial channels; preferably, the purity of the magnesium block is greater than 99.9wt.%, the magnesium-scandium master alloy is 80.0wt.%Mg-20.0wt.%Sc, and the magnesium-yttrium master alloy is 70.0wt.%Mg-30.0wt.%Y.

[0029] The present invention provides a heterostructured Mg-Sc-Y anode material, comprising the following components in percentage by mass: magnesium: 99.8%, scandium: 0.1%, and yttrium: 0.1%.

[0030] In one embodiment, the purity of the magnesium is preferably >99.9%, Mg-20.0wt.%Sc master alloy, Mg-30.0wt.%Y master alloy, and the oxide scale on the surface is polished off.

[0031] The present invention also provides a method for preparing the heterostructured Mg-Sc-Y anode material, comprising the following steps: (1) Under a protective atmosphere, a high-purity magnesium block, a high-purity magnesium-scandium master alloy and a high-purity magnesium-yttrium master alloy are melted to obtain an alloy liquid, a refining agent is added to the alloy liquid for refining, and after the refining is completed, casting and cooling are performed in sequence to obtain an ingot; (2) Under a protective atmosphere, the ingot is subjected to a two-stage solid solution treatment to obtain a solid solution matrix; (3) The solid solution matrix is ​​subjected to extrusion processing to obtain an extruded rod.

[0032] In one embodiment, the high-purity magnesium block, the high-purity magnesium-scandium master alloy, and the high-purity magnesium-yttrium master alloy all need to be dried before use. The drying temperature is preferably 180-220° C., more preferably 190-210° C., and more preferably 195-205° C. The drying holding time is preferably 100-140 min, more preferably 110-130 min, and more preferably 115-125 min.

[0033] In one embodiment, the sequence in step (1) is to raise the temperature of the resistance furnace to 400° C., put some magnesium blocks in the crucible, and introduce protective gas to form a protective atmosphere.

[0034] In one embodiment, the crucible needs to be pre-treated before use. The pre-treatment steps are: placing the crucible on a resistance furnace at a temperature of 300°C for 20 minutes, taking out the crucible after the insulation is completed, and evenly applying the coating on the surface of the crucible. The number of times of application is preferably 3 times, and the composition of the coating is preferably zinc oxide, water and sodium silicate. The mass volume ratio of zinc oxide, water and sodium silicate is preferably 22.5g:120mL:22.5g.

[0035] In one embodiment, the protective atmosphere in step (1) is preferably carbon dioxide and sulfur hexafluoride, and the volume ratio of carbon dioxide to sulfur hexafluoride is preferably (35-45):1, further preferably (37-43):1, and more preferably (39-41):1.

[0036] In one embodiment, after a protective gas is introduced to form a protective atmosphere, the temperature of the resistance furnace is adjusted to the melting temperature. After the magnesium block is melted to form magnesium liquid, a slag scoop is used to remove the oxide film on the surface of the magnesium liquid, and then the magnesium-scandium intermediate alloy is added to the magnesium liquid, and the remaining magnesium block is pressed onto the surface of the magnesium-scandium intermediate alloy for melting.

[0037] In one embodiment, the mass of the remaining magnesium block is greater than the mass of the magnesium-scandium master alloy. The purpose of pressing one of the remaining magnesium blocks onto the surface of the magnesium-scandium master alloy is to press the magnesium-scandium master alloy below the magnesium liquid level to promote the full melting of the magnesium-scandium master alloy.

[0038] In one embodiment, the skimmer needs to be pre-treated before use. The pre-treatment step is: place the skimmer on a resistance furnace at a temperature of 300°C for 20 minutes, take out the skimmer after the insulation is completed, and evenly apply a coating on the surface of the skimmer. The number of times of application is preferably 3 times, and the composition of the coating is preferably zinc oxide, water and sodium silicate. The mass volume ratio of zinc oxide, water and sodium silicate is preferably 22.5g:120mL:22.5g.

[0039] In one embodiment, the melting temperature in step (1) is preferably 710-750°C, more preferably 720-740°C, and more preferably 725-735°C.

[0040] In one embodiment, after the magnesium-scandium intermediate alloy is melted to obtain alloy liquid, the temperature of the resistance furnace is adjusted to the melting temperature again. After the magnesium block is melted to form magnesium liquid, a slag spoon is used to remove the oxide film on the surface of the magnesium liquid, and then the magnesium-yttrium intermediate alloy is added to the magnesium liquid, and the last remaining magnesium block is pressed onto the surface of the magnesium-yttrium intermediate alloy for melting.

[0041] In one embodiment, the pre-treatment and preferred temperature of the skimmer when in use are as above.

[0042] In one embodiment, after the magnesium-yttrium master alloy is melted to obtain a molten alloy, the system temperature is adjusted to a refining temperature for refining.

[0043] In one embodiment, the refining agent in step (1) is a mixture of MgCl2, KCl, BaCl2 and CaF2, and the mass ratio of MgCl2, KCl, BaCl2 and CaF2 is 46:40:8:6; The refining temperature is preferably 740° C., and the refining time is preferably 1-2 min, more preferably 1.2-1.8 min, and even more preferably 1.4-1.6 min.

[0044] In one embodiment, a stirring rod is used to stir the alloy liquid during the refining process.

[0045] In one embodiment, the stirring rod needs to be pre-treated before use. The pre-treatment steps are: place the stirring rod on a resistance furnace at a temperature of 300°C for 20 minutes, take out the stirring rod after the insulation is completed, and evenly apply the coating on the surface of the stirring rod. The number of times of application is preferably 3 times, and the composition of the coating is preferably zinc oxide, water and sodium silicate. The mass volume ratio of zinc oxide, water and sodium silicate is preferably 22.5g:120mL:22.5g.

[0046] In one embodiment, after refining is completed, the temperature is adjusted to the melting temperature for heat preservation, and after heat preservation is completed, the system temperature is adjusted to the temperature for slag removal treatment, and slag removal treatment is performed. The heat preservation time is preferably 15-25 minutes, more preferably 17-23 minutes, and more preferably 19-21 minutes; the temperature for slag removal treatment is preferably 700-720°C, more preferably 705-715°C, and more preferably 708-712°C.

[0047] In one embodiment, the tool for deslagging is a deslagging spoon, and the purpose of deslagging is to remove the oxide film on the surface of the alloy liquid.

[0048] In one embodiment, the skimmer needs to be pre-treated before use. The pre-treatment step is: place the skimmer on a resistance furnace at a temperature of 300°C for 20 minutes, take out the skimmer after the insulation is completed, and evenly apply a coating on the surface of the skimmer. The number of times of application is preferably 3 times, and the composition of the coating is preferably zinc oxide, water and sodium silicate. The mass volume ratio of zinc oxide, water and sodium silicate is preferably 22.5g:120mL:22.5g.

[0049] In one embodiment, after the slag removal process is completed, the alloy liquid is poured into a mold for casting to obtain a blank. The material of the mold is preferably copper, and the mold needs to be preheated before use, and the preheating temperature is preferably 200°C.

[0050] In one embodiment, the cooling method in step (1) is preferably air static cooling.

[0051] In one embodiment, the protective atmosphere in step (2) is preferably argon.

[0052] In one embodiment, the two-stage solution treatment in step (2) is performed in a heat treatment furnace of model OTF-1200X.

[0053] In one embodiment, the specific steps of the two-stage solution treatment in step (2) are preferably: a first solution treatment and a second solution treatment performed sequentially; The temperature of the first solution treatment is preferably 310-330°C, more preferably 315-325°C, more preferably 317-323°C, and the holding time of the first solution treatment is preferably 50-70min, more preferably 55-65min, more preferably 58-62min; The temperature of the second solution treatment is preferably 480-520°C, more preferably 490-510°C, more preferably 495-515°C, and the holding time of the second solution treatment is preferably 350-370min, more preferably 355-365min, more preferably 357-363min.

[0054] In one embodiment, after the double-stage solution treatment is completed, water quenching is performed to obtain a solid solution matrix.

[0055] In one embodiment, the solid solution matrix is ​​machined to form an extrusion blank, which is then subjected to an extrusion process to obtain an extruded rod. The extrusion process temperature is preferably 245° C., and the extrusion ratio is preferably 16:1.

[0056] The present invention also provides an application of a heterostructured Mg-Sc-Y anode material in a magnesium-air battery.

[0057] The present invention also provides a magnesium-air battery, comprising the above-mentioned heterostructure Mg-Sc-Y anode material.

[0058] Example 1 The high-purity magnesium block, the high-purity magnesium-scandium master alloy and the high-purity magnesium-yttrium master alloy are placed in an oven and dried at 200° C. for 2 h for later use.

[0059] The crucible was placed on a resistance furnace at 300°C for 20 minutes. After the heat preservation was completed, the crucible was taken out and the coating was evenly applied on the surface of the crucible three times. The coating composition was zinc oxide, water and sodium silicate, wherein the mass volume ratio of zinc oxide, water and sodium silicate was 22.5g:120mL:22.5g.

[0060] Place the skimmer on a resistance furnace at 300°C for 20 minutes, take out the skimmer after the end of the heat preservation, and evenly apply the coating on the surface of the skimmer for 3 times. The coating is composed of zinc oxide, water and sodium silicate, wherein the mass volume ratio of zinc oxide, water and sodium silicate is 22.5g:120mL:22.5g.

[0061] The stirring rod was placed on a resistance furnace at 300°C for 20 minutes. After the temperature was maintained, the stirring rod was taken out and the coating was evenly applied on the surface of the stirring rod for 3 times. The coating was composed of zinc oxide, water and sodium silicate, wherein the mass volume ratio of zinc oxide, water and sodium silicate was 22.5g:120mL:22.5g.

[0062] The resistance furnace was heated to 400°C, 365.2 g of the pretreated magnesium block was placed in the pretreated crucible, and a mixed gas of carbon dioxide and sulfur hexafluoride (the volume ratio of carbon dioxide and sulfur hexafluoride was 40:1) was introduced to form a protective atmosphere. The temperature of the resistance furnace was adjusted to 710°C and kept warm for 25 minutes. The magnesium block was melted to form magnesium liquid. The oxide film on the surface of the magnesium liquid was removed with a slag spoon, and then the pretreated magnesium-scandium intermediate alloy was added, and then a second 65.0 g pretreated magnesium block was pressed onto the surface of the magnesium-scandium intermediate alloy. After the magnesium-scandium intermediate alloy and the magnesium block were melted to obtain an alloy liquid, the temperature was adjusted to the melting temperature of the alloy again, and then the magnesium-yttrium intermediate alloy was added to the magnesium liquid, and the last remaining magnesium block was pressed onto the surface of the magnesium-yttrium intermediate alloy for melting. Then the system temperature is cooled to 740℃, and a refining agent (the mass ratio of MgCl2, KCl, BaCl2 and CaF2 is 46:40:8:6) is added, and the alloy liquid is stirred for 2 minutes with a stirring rod for refining. After the refining is completed, the temperature is adjusted to 740℃, and the temperature is kept at 740℃ for 20 minutes. After the insulation is completed, the system temperature is adjusted to 710℃ for slag removal to remove the oxide film on the surface of the alloy liquid. After the slag removal is completed, the alloy liquid is poured into a preheated 200℃ copper mold for casting under the condition of a mixed gas of carbon dioxide and sulfur hexafluoride (the volume ratio of carbon dioxide and sulfur hexafluoride is 40:1) to obtain a blank. The blank is cooled in air to obtain an ingot.

[0063] Under argon atmosphere, the ingot was placed in an OTF-1200X heat treatment furnace for a two-stage solution treatment, wherein the first-stage solution treatment was carried out at 320°C for 60 minutes, and the second-stage solution treatment was carried out at 500°C for 360 minutes. After the two-stage solution treatment was completed, water quenching was performed to obtain a solid solution matrix.

[0064] The solid solution matrix is ​​machined into an extruded billet with a diameter of 40 mm and a height of 50 mm, and then hot extruded at 245° C. with an extrusion ratio of 16:1 to obtain an extruded rod, which is a heterostructured Mg-Sc-Y anode material.

[0065] Performance Testing The heterostructured Mg-Sc-Y anode material obtained in Example 1 was placed under a metallographic microscope for observation. The specific crystal phase organization diagram is shown in the figure below. Figure 1 As shown, from Figure 1 It can be seen that the heterostructured Mg-Sc-Y anode material provided by the present invention has no precipitated phase, and the metallographic structure is composed of fine equiaxed crystals and deformed coarse crystals.

[0066] The average grain size of the fine crystals of the heterostructured Mg-Sc-Y anode material obtained in Example 1 was tested, and the results were as follows: Figure 2 As shown, according to the Nano measure test software, the average grain size is tested to be 1.30±0.01μm, and the aspect ratio of the deformed coarse grain is 6.73±0.01.

[0067] The heterostructured Mg-Sc-Y anode material obtained in Example 1 was characterized and tested. Figure 3 As shown. Figure 3 a in the figure is the SEM microstructure diagram. Figure 3 b in the figure is the XRD pattern. Figure 3 It can be seen that the heterostructured Mg-Sc-Y anode material provided by the present invention has only a single phase of α-Mg.

[0068] Electrochemical tests were performed using a typical three-electrode system electrochemical workstation of Wuhan Coster CS350H model, wherein a platinum sheet was an auxiliary electrode, the heterostructure Mg-Sc-Y anode material prepared in Example 1 of the present invention was a working electrode, a saturated calomel electrode was a reference electrode, and the electrolyte used was a 3.5wt% NaCl solution.

[0069] The electrochemical test includes open circuit potential test, impedance spectrum test and dynamic potential polarization test. The test is carried out according to the following process. First, the open circuit potential test is carried out for 1 hour. After the open circuit potential is stable, the impedance spectrum test is carried out. The frequency is set to 100kHz-10mHz and the voltage is 5mV. Finally, the dynamic potential polarization test is carried out with a scanning speed of 0.1mV / s and a scanning range of -2.4V to -1V. The specific results are as follows: Figure 4 As shown in the figure, the polarization curve was analyzed by CorShow software, and the slope of the anode branch was 54.66, the slope of the cathode branch of the polarization curve was 321.74, and the corrosion current density was 369.69μA / cm 2 .

[0070] Example 2 The same as Example 1, except that the anode material is not subjected to extrusion treatment after the double-stage solid solution treatment. Example 3 The same as Example 1, except that the cooled ingot is not subjected to the two-stage solution treatment and extrusion treatment. Example 4 The same as Example 1, except that the anode material is replaced with a Mg-Sc-In alloy, whose mass percentage components are magnesium: 99.8%, scandium: 0.1%, and indium: 0.1%, and the same process is used in the preparation process. Example 5 The same as Example 1, except that the anode material is replaced with recast high-purity magnesium and subjected to the same homogenization and extrusion treatments. The anode materials obtained in Examples 1-5 were used as anodes of air magnesium batteries.

[0071] The performance of Example 1 was tested at different discharge current densities, and the results are shown in Table 1.

[0072] Table 1 Performance test results of Example 1 at different discharge current densities It can be seen from Table 1 that the energy density of the heterostructured Mg-Sc-Y anode material provided by the present invention increases with the increase of current density, and the highest data in the table is 1915.59 mW·h·g -1 .

[0073] Test Example 1 and other examples as anode materials at a discharge current density of 10 mA cm -2 The battery performance under the condition of . The results are shown in Table 2.

[0074] Table 2 Examples 1-5 at a discharge current density of 10 mA·cm -2 Battery performance test results It can be seen from Table 2 that at 10 mA cm -2 The heterostructured Mg-Sc-Y anode material provided by the present invention exhibits better average discharge voltage, anode efficiency and energy density than other embodiments, and is a magnesium-air battery electrode material with great development potential.

[0075] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.

Claims

1. A heterostructured Mg-Sc-Y anode material, characterized in that: The invention comprises the following components in percentage by mass: scandium: 0.1%, yttrium: 0.1%, and the balance being magnesium.

2. The heterostructured Mg-Sc-Y anode material according to claim 1, characterized in that: The heterogeneous structure Mg-Sc-Y anode material presents a heterogeneous microstructure, which is composed of elongated deformed grains and fine equiaxed grains.

3. The heterostructured Mg-Sc-Y anode material according to claim 2, characterized in that: The average grain size of the fine equiaxed grains is 1.30±0.01 μm, and the aspect ratio of the elongated deformed grains is 6.73±0.

05.

4. A method for preparing the heterostructured Mg-Sc-Y anode material according to any one of claims 1 to 3, characterized in that: The following steps are involved: (1) Under a protective atmosphere, a magnesium block, a magnesium-scandium master alloy and a magnesium-yttrium master alloy are melted to obtain an alloy liquid, stirred and allowed to stand, scum on the surface is scraped off, a refining agent is added to the alloy liquid for refining, and after the refining is completed, casting and cooling are performed in sequence to obtain a Mg-Sc-Y alloy ingot; (2) Under a protective atmosphere, performing a double-stage solid solution treatment on the Mg-Sc-Y alloy ingot to obtain a solid solution matrix; (3) The solid solution matrix is ​​subjected to extrusion processing to obtain an extruded rod, which is a heterostructured Mg-Sc-Y anode material.

5. The method for preparing the heterostructured Mg-Sc-Y anode material according to claim 4, characterized in that: In step (1), the protective atmosphere is carbon dioxide and sulfur hexafluoride, and the volume ratio of carbon dioxide to sulfur hexafluoride is (35-45):1; In step (2), the protective atmosphere is argon.

6. The method for preparing the heterostructured Mg-Sc-Y anode material according to claim 4, characterized in that: In step (1), the refining agent is a mixture of MgCl2, KCl, BaCl2 and CaF2, and the mass ratio of MgCl2, KCl, BaCl2 and CaF2 is 46:40:8:6; The refining temperature is 740° C., and the refining time is 1-2 minutes.

7. The method for preparing the heterostructured Mg-Sc-Y anode material according to claim 4, characterized in that: In step (2), the steps of the double-stage solution treatment are: a first solution treatment and a second solution treatment performed sequentially; The temperature of the first solution treatment is 310-330°C, and the holding time of the first solution treatment is 50-70min; The temperature of the second solution treatment is 480-520° C., and the holding time of the second solution treatment is 350-370 min.

8. The method for preparing the heterostructured Mg-Sc-Y anode material according to claim 4, characterized in that: In step (3), the extrusion treatment temperature is 240-250° C., the extrusion treatment speed is 0.08-0.12 mm / s, and the extrusion ratio is 15:1-17:

1.

9. Use of the heterostructured Mg-Sc-Y anode material according to any one of claims 1 to 3 in a magnesium-air battery.

10. A magnesium-air battery, characterized in that: The heterostructured Mg-Sc-Y anode material comprises the heterostructured Mg-Sc-Y anode material according to any one of claims 1 to 3.

Citation Information

Patent Citations

  • High-intensity welding wire for aluminum-zinc-magnesium-scandium alloy and preparing method thereof

    CN103273214A

  • Absorbable orthopedic implanted magnesium alloy and preparation method thereof

    CN108330367A

  • Corrosion-resistant ternary magnesium alloy and preparation method thereof

    CN111155016A

  • Magnesium-silver alloy and preparation method and application thereof

    CN116024470A

  • Mg-Sc magnesium alloy with high corrosion resistance and preparation method thereof

    CN117127074A